Do Employee Experience Has an Impact to Turnover? - Achmad Mohyi; Dewi Sukmawati (Universitas Muhammadiyah Malang, 2023)
The growing development of the F&B industry, especially coffee shop SMEs, is of course proportional to the large number of absorbed Indonesian workers. This is inseparable from the problem of high employee turnover. A high turnover rate in a company is closely related to a bad employee experience. Employee experience is basically an employee's perception of their work experience in a company. This study aims to see how employee experience can affect the turnover rate in a business. This research technique uses a qualitative study with purposive sampling technique. In this research interviews were conducted with employees and ex-employees in 3 different coffee shops. The results of this study indicate that high turnover rates are caused by poor employee experience. Where in this case employees do not have a sense of belonging to the compan